Independent Mobility and Social Affordances of Places for Urban Neighborhoods: A Youth-Friendly Perspective - Lopes, Frederico; Cordovil, Rita; Neto, Carlos (Frontiers in Psychology, 2018)
Meaning of place is usually approached as slow social cognitive construction. However, grounded on the theory of affordances, it may also stem from direct perception-action processes, which enable the formation of immediate perceived functional, social or symbolic meaning of place (Raymond, Kyttä, & Stedman, 2017). In the present study, affordances of places, which are perceived by a specific perceiver in a specific place, were mapped using a web-map survey. Each place offers opportunities for interaction, behavior, use, feeling or meaning, which is directly perceived and actualized there. This paper aims at identifying the degree of youth-friendliness of urban neighborhoods using the hypothetical intertwined model of independent mobility and actualized affordances (Kyttä, 2004) combined with place use and meaning (Broberg, Kyttä, & Fagerholm, 2013). SoftGISchildren methodology (Broberg, Kyttä, et al., 2013) was adopted to carry out a cross-sectional research, involving 145 sixth to ninth graders of the Great Lisbon area. SoftGIS integrates Public Participation Geographic Information Systems (PPGIS), enabling collection and place mapping of daily subjective environmental experiences in the physical environment, consequently allowing for individuals to be actively engaged in public processes of participation (Brown & Kyttä,2014). A place based web survey called “Ideal City: a game of graphic imagination” was adopted. Participants were asked to map their home place, select and mark social, functional, leisure and emotional place transactions, and report actual and ideal mobility to these places. Findings on mobility showed that shorter distances to meaningful affordances of places promote active and independent travel; ideally, youths would like to be more frequently active and more frequently autonomous. As for meaningful places, a total of 1632 affordances were localized, with a higher number on social category. Neighborhood area (500 meters around home place) was assessed as youth-friendly, where active and independent travel occurred more frequently, and social affordances were the most expressive type. Relational and affectional experience in the neighborhood places was meaningful for youth. Municipalities should consider these features when planning, designing and managing residential areas aiming for the well-being and health of young citizens; and include youths as specialists of space (spatialists) in planning participatory processes (PPGIS).